High-order harmonic generation from ions in a capillary discharge - Rocca, Jorge J., author; Kapteyn, Henry C., author; Murnane, Margaret M., author; Walker, Barry C., author; Cohen, Oren, author; Berrill, Mark, author; Grisham, Michael, author; Popmintchev, Tenio, author; Reagan, Brendan, author; Gaudiosi, David M., author; American Physical Society, publisher (Colorado State University. Libraries, 2006)
We demonstrate a significant extension of the high-order harmonic cutoff by using a fully-ionized capillary discharge plasma as the generation medium. The preionized plasma dramatically reduces ionization-induced defocusing and energy loss of the driving laser due to ionization. This allows for significantly higher photon energies, up to 150 eV, to be generated from xenon ions, compared with the70 eV observed previously. We also demonstrate enhancement of the harmonic flux of nearly 2 orders of magnitude at photon energies around 90 eV when the capillary discharge is used to ionize xenon, compared with harmonic generation in a hollow waveguide. The use of a plasma as a medium for high-order harmonic generation shows great promise for extending efficient harmonic generation to much shorter wavelengths using ions.